Visualizing non-linear control system performance by means of multidimensional scaling - Tenreiro Machado, J. A. (2011)
This paper addresses the use of multidimensional scaling in the evaluation of control system performance. Both linear and non-linear systems are analysed based on the closed loop time response under the action of a reference step input signal. Two alternative performance indices, based on the time and frequency domains, are tested. The numerical experiments demonstrate the feasibility of the proposed methodology and motivate its extension for other performance measures and a broader classes of non-linearities.